Literary transactions in South Africa a politics of interpretation - Chapman, Michael 1945- (Bloomsbury Academic, 2025)
"A representative overview of some of the most pressing concerns in contemporary literary criticism in South Africa, demonstrating literary form's shaping power in the interpretation of politically contentious content. Rather than pressing literature into the service of a political cause or programme, this study's purpose – its politics of interpretation – is to open literature to the potential of human experience in both the personal and the public life. The society of focus – South Africa – is a society of political contestation. Instead of prioritizing thewhatof contestation, however, Michael Chapman explores contestation through thehowof the literary work. In sharp transactions between an intransitivity of form and a compulsion to communicate, the book elucidates an ethics of aesthetics in J. M. Coetzee and Nadine Gordimer, and the best of modernism and the worst of modernism in Roy Campbell’s poetry. It also asks: Can Themba’s ‘style’ of the shebeens in the 1950s be re-visited in a contemporary context of gender-based abuse? Why or how are Ellen Kuzwayo and Mtutuzeli Matshoba, writing in the ‘struggle’ years of the 1970s, simultaneously less than artists and more than artists? Has the interpretative frame of the ‘postcolonial’ best served fiction after apartheid? What language of interpretation best releases the voices of contemporary women’s poetry: a poetry which in its play on identities and identifications looks both inwards to its locality and outwards to the globe? Alert to both South Africa’s colonial past and its assertions of today,Literary Transactions in South Africapursues the challenge of interpreting a literature of disjuncture between Africa and the West, or the South and the North."
Informationen wurden der Landingpage entnommen, da weder Titelseite noch Impressum vorhanden (Bloomsbury Collections)
Keywords: Politics in literature; South African literature / History and criticism; Literary studies: post-colonial literature; Literary theory; Philosophy: aesthetics